THE IMPORTANCE OF THE CORRECT CHOICE OF METHODS OF UPBRINGING IN THE EDUCATIONAL PROCESS (Scientific journal of the Fergana State University, 2024)
The importance of modern teaching in the process of teaching pedagogy requires the conformity of universal and national practice. Educational, educational and developmental objectives are implemented only after the analysis of their individual traits. The article fully describes how to solve the various tasks with the students in the technical and educational environments and the conditions of the pedagogical tactic in a clear, prompt and effective manner.